On Human Remains: Excavating the Home Archive - Kirk, David; Sellen, Abigail (Microsoft, 2008)
Creating digital archives of personal and family memories is an area of growing interest, but which seemingly is often not supported by a thorough understanding of current home archiving practice. In this paper we seek to excavate the home archive. Based on extensive field research in family homes we present a taxonomy of the kinds of sentimental objects to be found in homes, and through in-depth interviews with family members, we explore why and how those objects are kept and archived within the home. From this understanding of existing practice we derive requirements and implications for the design of digital archiving or memory technologies.